KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, PROFITABILITAS, DAN STRUKTUR ASET TERHADAP KEBIJAKAN HUTANG (STUDI EMPIRIS PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI TAHUN 2012-2014) - Marlynda, Evelyne Maharani; Ashari, Ashari (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2017)
Institutional Ownership, Devidend Policy, Size of Company, Profitability, and Structure Assests on Debt Policy (Empirical Study on Property Company Which Registerd in IDX Year 2012-2014). The purpose of this research was to determine the effect institutional ownership, dividend policy, firm size, profitability, and asset structure on debt policy. The data used in this research were obtained from the company’s annual report period of 2012-2014 from www.idx.co.id. The population of this research was all property companies listed in IDX. This research used purposive sampling and the criteria that must be fulfilled were property companies listed in IDX period of 2012-2014, published their financial statement during the period of the research, the property companies which have institutional ownership, the companies which have complete financial data to calculate variables in this research, and distributed dividend in period of this research, the sample 17 company’s which fulfilled. The data analysis method that used in this research are multiple regression analysis. The result of this research show that dividend policy and firm size didn’t have effect on debt policy. Institutional ownership and asset structure have negative significant effect on debt policy. Profitability has positive significant effect on debt policy.